THE SIGNIFICANCE OF PEDAGOGICAL INTERNSHIPS IN ThE PROCESS OF PREPARING STUDENTS FOR THE TEACHER’S PROFESSION - Minchanowska, Aleksandra; Hruzd-Matushchyk, Alisa (The Modern Higher Education Review, 2017)
Educating children, youth and, later in life, adults has always been a fundamental duty of every society. The current transformations taking place in the social life and the educational reforms in Poland necessitate due reflection upon a new model of educating future teachers. Their education based on the designs and curricula of university studies comprises both theoretical and practical classes. Theory and practice are interwoven into a coherent entity and constitute a source of knowledge legitimized in the process of teachers’ education. The research object of this study is the education of pedagogy students with particular focus on the significance of pedagogical internships in the preparation for the teaching career. The text is divided into several sections. The first is devoted to the role of pedagogical internships in preparing future teachers for performing their profession as well as to the platforms of teachers’ pedagogical activity. The next part comprises a presentation of a fragment of authors’ own (cyclic) research conducted among students of teaching courses. The article is complemented by conclusions.